Fibre failure assessment in carbon fibre reinforced polymers under tensile loading using in situ synchrotron X-ray computed tomography. (March 2022) - Rosini, Sebastian; Mavrogordato, Mark N; Takano, Tsuneo; Sugiura, Naoki; Spearing, S Mark; Sinclair, Ian
In situ synchrotron radiation computed tomography (SRCT) was used to compare the fibre damage progression in five configurations of (902 /02 )s carbon-epoxy coupons loaded to failure. The effects of different sizing types, surface treatments and fibre diameters on the macroscopic properties, for example, ultimate tensile strength (UTS), and on the damage accumulation at a microscopic scale, for example, fibre break accumulation, were assessed. A semi-automated approach was adopted to process the large amount of data obtained from the SRCT scans and further method applicability areas can be envisaged. Single fibre break accumulation was seen to be influenced by the fibre type, while the formation of interacting fibre break groups by the surface treatment and the sizing type. For the materials presented, it can be suggested that an increased defect tolerance can be obtained by moving from stronger to weaker fibre-matrix adhesion, with sub-critical multiplet behaviour emerging as independent of the average UTS value.